2005
DOI: 10.1167/iovs.04-1142
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Novel Vital Dyes for Intraocular Surgery

Abstract: The systematic evaluation of dyes for intraocular use seems mandatory. In this study four dyes were identified with effective staining characteristics, with two of these dyes having no detectable toxic effect on RPE cells in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 43 publications
1
42
0
3
Order By: Relevance
“…In comparison to six biological stains (light green yellowish, E68, Chicago blue, rhodamine, rhodulinblau-basic) BroB has stained the ERM and ILM better with no RPE-cell in vitro toxicity or primary proliferation at concentrations of 0.2 and 0.02% (58) . In vivo studies in rodent and porcine eyes demonstrated that BroB at concentrations of 0.5 and 0.02% promoted less retinal toxicity as assessed by histology and ganglion cell counts in comparison to three other vital dyes (light-green, Chicago blue, and E68).…”
Section: Bromophenol Bluementioning
confidence: 94%
“…In comparison to six biological stains (light green yellowish, E68, Chicago blue, rhodamine, rhodulinblau-basic) BroB has stained the ERM and ILM better with no RPE-cell in vitro toxicity or primary proliferation at concentrations of 0.2 and 0.02% (58) . In vivo studies in rodent and porcine eyes demonstrated that BroB at concentrations of 0.5 and 0.02% promoted less retinal toxicity as assessed by histology and ganglion cell counts in comparison to three other vital dyes (light-green, Chicago blue, and E68).…”
Section: Bromophenol Bluementioning
confidence: 94%
“…Em comparação com outros agentes biológicos, o Brbcora bem a MER e MLI sem toxicidade ao EPRin vitro com concentrações de0.2% e 0.02%. 55 Estudos In vivoem roedores e olhos de porcinos mostraram que essa substância em concentrações de 0.5% e 0.02% promovem menos dano retiniano, evidenciado pela histologia e contagem de células ganglionares, em comparação com três outros corantes (Light-green, Azul Chicago e E68).…”
Section: Azul De Bromofenolunclassified
“…71 Recently, several other dyes, including infracyanine green, patent blue, bromophenol blue and brilliant blue have been proposed as possible tools in chromovitrectomy. [72][73][74][75][76][77][78][79][80] Although intra-operative application of vital dyes has facilitated surgical techniques and outcomes in recent years, controversy still remains Diagnosing and Treating Vitreomacular Adhesion The ability to treat and even prevent the complications of early-stage PVD will expand as safe and effective pharmacological methods for inducing PVD become available. 10 The goals of pharmacological vitreolysis are to induce liquefaction of the vitreal gel and promote complete dehiscence of the vitreous from the retina.…”
Section: -64mentioning
confidence: 99%